The Fast-Evolving phy-2 Gene Modulates Sexual Development in Response to Light in the Model Fungus Neurospora crassa - Zheng Wang (American Society for Microbiology, 2016)
ABSTRACT Rapid responses to changes in incident light are critical to the guidance of behavior and development in most species. Phytochrome light receptors in particular play key roles in bacterial physiology and plant development, but their functions and regulation are less well understood in fungi. Nevertheless, genome-wide expression measurements provide key information that can guide experiments that reveal how genes respond to environmental signals and clarify their role in development. We performed functional genomic and phenotypic analyses of the two phytochromes in Neurospora crassa, a fungal model adapted to a postfire environment that experiences dramatically variable light conditions. Expression of phy-1 and phy-2 was low in early sexual development and in the case of phy-2 increased in late sexual development. Under light stimulation, strains with the phytochromes deleted exhibited increased expression of sexual development-related genes. Moreover, under red light, the phy-2 knockout strain commenced sexual development early. In the evolution of phytochromes within ascomycetes, at least two duplications have occurred, and the faster-evolving phy-2 gene has frequently been lost. Additionally, the three key cysteine sites that are critical for bacterial and plant phytochrome function are not conserved within fungal phy-2 homologs. Through the action of phytochromes, transitions between asexual and sexual reproduction are modulated by light level and light quality, presumably as an adaptation for fast asexual growth and initiation of sexual reproduction of N. crassa in exposed postfire ecosystems. IMPORTANCE Environmental signals, including light, play critical roles in regulating fungal growth and pathogenicity, and balance of asexual and sexual reproduction is critical in fungal pathogens’ incidence, virulence, and distribution. Red light sensing by phytochromes is well known to play critical roles in bacterial physiology and plant development. Homologs of phytochromes were first discovered in the fungal model Neurospora crassa and then subsequently in diverse other fungi, including many plant pathogens. Our study investigated the evolution of red light sensors in ascomycetes and confirmed—using the model fungus Neurospora crassa—their roles in modulating the asexual-sexual reproduction balance in fungi. Our findings also provide a key insight into one of the most poorly understood aspects of fungal biology, suggesting that further study of the function of phytochromes in fungi is critical to reveal the genetic basis of the asexual-sexual switch responsible for fungal growth and distribution, including diverse and destructive plant pathogens.